Development of caffeine‐encapsulated alginate‐based matrix combined with different natural biopolymers, and evaluation of release in simulated mouth conditions. (3rd May 2018) - Mohammadi, Nima; Ehsani, Mohammad Reza; Bakhoda, Hossein
Abstract: Caffeine was encapsulated into calcium alginate microcapsules, and these microcapsules were produced with four types of material – starch, xanthan, chitosan, and whey protein isolate – in combination with alginate. Formulation characteristics such as the efficiency of microencapsulation, microcapsule size, viscosity, and texture properties of the microcapsules have been evaluated. The release of caffeine from different microcapsules was conducted in simulated saliva fluid. Alginate microcapsules with chitosan coating provided the slowest release of caffeine, compared with the other microcapsules. Significant differences in the appearance of the microcapsules were detectable by scanning electron microscopy (SEM) and optical microscopy. Fourier‐transform infrared spectrometry (FTIR) analysis confirmed the existence of carbonyl groups in caffeine‐loaded microcapsules, and differential scanning calorimetry (DSC) thermograms indicated the glass transition temperature of the microcapsules. This study showed that the microencapsulation of caffeine with alginate may be helpful for designing fast (alginate) as well as prolonged caffeine release (alginate–starch–xanthan with chitosan). Abstract : The microcapsules loaded with caffeine were globular in shape and the starch granules were present in alginate matrix. The presence of starch granules was shown in by Lugol's iodine solution at 40× magnification.